2000
DOI: 10.1007/bf03020729
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical nerve stimulation does not augment combined spinal epidural labour analgesia

Abstract: Purpose: The spinal portion of the combined spinal epidural technique (CSE) provides dramatic but limited labour analgesia. Transcutaneous Electrical Nerve Stimulation (TENS) has been noted to modulate pain, 1 in part by the frequency of stimulation chosen. 2 Because nerve action potentials are blocked by local anesthestics in a frequency dependent manner, 3 we speculated that a TENS unit could increase the quality and duration of the spinal portion of a CSE.Methods: Forty parturients in active spontaneous lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…The parameters of stimulation are determinant for TENS therapy to be successful . For Wang et al ., the frequency, amplitude and time of treatment caused diverging results.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of stimulation are determinant for TENS therapy to be successful . For Wang et al ., the frequency, amplitude and time of treatment caused diverging results.…”
Section: Discussionmentioning
confidence: 99%
“…TENS performed to the back has been compared with control groups and various modalities during labor pain, and there was no significant difference between TENS and other groups in the number of women undergoing cesarean section or assisted vaginal delivery [22,23,25]. Chao et al [24] have reported that, while TENS used during labor pain did not increase the cesarean rate, it tended to significantly increase assisted delivery (RR: 4.50).…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, TENS is used for the relief of pain for all types of musculoskeletal pain including LBP of any etiology. TENS has been increasingly and safely used especially for pain relief during labor and delivery [20,21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…A TENS proporciona analgesia pós-operatória com evidente redução no consumo de analgésicos. Ela tem sido usada com relativo êxito no tratamento de dores aguda e crônica, mas o resultado no trabalho de parto e na cesariana não foi conclusivo em sua combinação com a anestesia regional [61][62][63][64][65][66] .…”
Section: Estimulação Elétrica Nervosa Transcutânea (Tens)unclassified
“…TENS provides for postoperative analgesia, reducing the dose of analgesics taken. It has been used with relative success to treat acute and chronic pain, but the result in labor and cesarean section is nonconclusive when combined with regional anesthesia [61][62][63][64][65][66] .…”
Section: Transcutaneous Electrical Nervous Stimulation (Tens)mentioning
confidence: 99%